Airway management in adults with cervical spine injury - ERDEN, Aydın; KANBUROĞLU, Çiğdem (Acta Medica, 2017)
Cervical spine injury is a dangerous, complex and challenging task of trauma. Airway management is crucial in patients with cervical spine injury as airway management techniques may cause secondary neurological injury. Therefore, learning how to manage the airway in trauma patients has profound importance. In this review, we aimed to highlight airway management in adults with cervical spine injury and discuss areas of uncertainty and limitations Key words: Cervical spine injury, immobilization, intubation, airway management